Significance of Hematological Parameters in Determining Prognosis of Acute Ischemic Stroke - Butt, Natasha Tahir (International Journal of Pathology, 2023)
Abstract: Stroke is the second most common cause of death worldwide. Various studies have highlighted the prognostic importance of hematological parameters in acute ischemic stroke including Erythrocyte Sedimentation Rate (ESR), C Reactive protein (CRP), Mean Platelet Volume (MPV), Total Leukocyte Count (TLC), platelet count, and hemoglobin.Objectives: To determine the prognosis of acute ischemic stroke and compare mean hematological parameters based on the prognosis of acute ischemic stroke.Material and Methods: 130 patients fulfilling the selection criteria were selected. Blood sample from each patient was obtained .Analysis for CRP and ESR obtained. Patients with acute ischemic stroke presenting within 72 hrs of the onset of symptoms of stroke were included. Correlation for the association between Outcome with Hemoglobin, TLC, Platelet, MPV, ESR & CRP. Means comparison between Expired group & Discharged group with Hemoglobin, TLC, Platelet, MPV, ESR and CRP using Independent sample’s t-test done. A p-value of < - 0.05 was taken as statistically significant.Results: Our findings showed that mean SD for quantitative variables like Hemoglobin, total leukocyte count, platelet, mean platelet volume, ESR & CRP were 10.2 2.9, 14.5 11.0, 142.4 93.8, 16.5 10.4, 42.3 35.9 & 18.5 23.4 respectively. There were 52.3% of patients who were expired and 47.7% of patients who were discharged. There was an association between outcomes of the patients with the variables like Hemoglobin, TLC, Platelet, MPV, ESR & CRP as all p-values are significant i.e.; 0.011, 0.020, 0.024, 0.000, 0.026 & 0.013 . Moreover, total leukocyte count, mean platelet volume, ESR & CRP are inversely proportional to the patients who expired or were discharged. Means comparison for the Expired group & Discharged group with Hemoglobin, TLC, Platelet, MPV, ESR & CRP are 9.56 & 11.02, 17.38 & 11.54, 126.22 & 160.27, 19.88 & 12.82, 49.91 & 34.10 & 25.47 & 10.86 respectively. The mean Discharged group is greater than the mean Expired group in Hemoglobin and Platelet. Mean Expired group is greater than the mean Discharged group in TLC, MPV, ESR & CRP.Conclusion: We concluded that a significant change was found in hematological parameters in ischemic stroke patients. In light of our results that depicted the difference in the readings of the values for each parameter like hemoglobin, erythrocyte sedimentation rate, platelets count, mean platelet volume, c-reactive protein, and leukocyte count we suggest that these hematological parameters can be used as a tool to take the measures necessary for the prevention of future damage by stroke.